AUTOBIOGRAPHICAL MOTIFS IN ABDULLA QAHHOR’S “TALES FROM THE PAST” - Kakharova Mohigul Yusufovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article explores the autobiographical elements and literary significance of Uzbek writer Abdulla Qahhor's life and works, with a particular focus on his story From the Past Tales. Through vivid recollections of his youth, Qahhor conveys a deep emotional landscape that aligns personal memory with broader social commentary. His development as a writer is also examined in comparison with Jack London, revealing parallels in thematic focus, literary method, and autobiographical resonance. Ultimately, the article argues that Qahhor‟s integration of personal experience and social critique exemplifies the power of autobiographical fiction to reflect individual struggles.